Blunt force trauma in the Canarian houbara bustard (Chlamyd-otis undulata fuertaventurae) produced by collision with overhead lines - C.M. Suárez-Santana; L. Marrero-Ponce; J. Navarro-Sarmiento; C. Rivero Herrera; R. Grandía Guzmán; A. Colom-Rivero; Ó. Quesada-Canales; E. Sierra; A. Fernández (Journal of Comparative Pathology, 2025)

Detection of highly pathogenic avian influenza H5N1 in marine mammals from South America - E. Sierra; M. Ulloa; C. Fiorito; A. Colom-Rivero; V. Neira; A. Fernández (Journal of Comparative Pathology, 2025)

Comparative assessment of microplastic ingestion among deep sea decapods: Distribution analysis in Sardinian and Catalan waters - L. Chiacchio; A. Cau; A. Soler-Membrives; M.C. Follesa; A. Bellodi; E. Carreras-Colom (Environmental Research, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Spatial and temporal variation in the prevalence of illegal lead shot in reared and wild mallards harvested in England - Emily A. Strong; Sarah L. Crowley; Julia L. Newth; Michelle F. O'Brien; Rosa Lopez Colom; Sean A. Davis; Ruth L. Cromie; Stuart Bearhop; Robbie A. McDonald (Environmental Pollution, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Factors shaping the abundance of two butterflies sharing resources and enemies across a biogeographic region - P. Colom; A. Traveset; M. R. Shaw; C. Stefanescu (Journal of Biogeography, 2024)
Aim Intraspecific variation in species relative abundance is shaped by a complex interplay of abiotic and biotic factors, making it both necessary and challenging to assess their combined relative importance in explaining variations across space and time. We used two congeneric butterfly species for which extensive count data and a deep understanding of their natural history is available to test three hypotheses explaining intraspecific variation in their abundance: (H1) seasonal dispersal behaviour driven by climate, (H2) resource availability and (H3) apparent competition mediated via shared parasitoids. Taxon Gonepteryx rhamni (Brimstone) and G. cleopatra (Cleopatra). Location NE Iberian Peninsula, where both species coexist, and a nearby archipelago (Balearic Islands), where only Cleopatra occurs. Methods We analysed spatial abundance variations for both species in the mainland and island–mainland differences in the abundance of Cleopatra. Abiotic and biotic factors, including temperature, host plant and overwintering habitat availability, larval parasitism and density dependence, were tested to explain the observed variations. Results H1 can explain variation in butterfly abundance between mainland regions since in warmer summers populations increased in cooler areas but decreased in warmer areas. H2 explains the variation within mainland climate regions with a strong positive relationship between resource availability and abundance but is unlikely to explain the island–mainland variation in the abundance of Cleopatra. H3 could neither explain biogeographical variation in abundance because although richer parasitoid communities were found on the mainland, larval mortality rates were similar or lower on the mainland than in the islands. Main Conclusions Climate and resource availability jointly account for variation in butterfly abundance across the mainland, but neither these factors nor parasitism can explain island–mainland differences. Both coexisting butterfly species and their larval parasitoids may have undergone evolutionary processes, resulting in spatial segregation that promotes the coexistence of the two butterfly species on the mainland.

Comparative microplastic load in two decapod crustaceans Palinurus elephas (Fabricius, 1787) and Nephrops norvegicus (Linnaeus, 1758) - Alessandro Cau; Pankaj A. Gorule; Andrea Bellodi; Ester Carreras-Colom; Davide Moccia; Lucia Pittura; Francesco Regoli; Maria Cristina Follesa (Marine Pollution Bulletin, 2023)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Nicotine-Mediated ADP to Spike Transition: Double Spiking in Septal Neurons - Sodikdjon A. Kodirov; Michael Wehrmeister; Luis Colom (The Journal of Membrane Biology, 2016)

Antifeedant and toxic effects of acetogenins from Annona montana on Spodoptera frugiperda - L. Di Toto Blessing; O. Álvarez Colom; S. Popich; A. Neske; A. Bardón (Journal of Pest Science, 2010)

Native fructose extracted from apple improves glucose tolerance in mice - C. Dray; A. Colom; C. Guigné; S. Legonidec; A. Guibert; F. Ouarne; P. Valet (Journal of Physiology and Biochemistry, 2009)

Toxic effects of annonaceous acetogenins from Annona cherimolia (Magnoliales: Annonaceae) on Spodoptera frugiperda (Lepidoptera: Noctuidae) - O. Álvarez Colom; A. Neske; S. Popich; A. Bardón (Journal of Pest Science, 2007)

A halocin acting on Na+/H+ exchanger of Haloarchaea as a new type of inhibitor in NHE of mammals - J. L. Lequerica; J. E. O’Connor; L. Such; A. Alberola; I. Meseguer; M. Dolz; M. Torreblanca; A. Moya; F. Colom; B. Soria (Journal of Physiology and Biochemistry, 2006)

Psoas abscess in patients infected with the human immunodeficiency virus - V. Navarro Lpez; F. Lpez Garca; E. Gonzlez Escoda; J. Gregori Colom; A. Muoz Prez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)